Promoting waste prevention in industry : search for policy instruments - Lilja, Raimo (Aalto University publication series, ISSN 1799-4942, 2016)
Jätteen määrä ja haitallisuuden ehkäisy teollisuudessa - ohjauskeinoja etsimässä.
Keywords: Pollution prevention; avfallshantering; cirkulär ekonomi; edistäminen; ekoeffektivitet; ekotehokkuus; främjande; industriavfall; jätehuolto; kiertotalous; miljöpolitik; miljötillstånd; ohjauskeinot; styrmedel; teollisuusjätteet; ympäristöluvat; ympäristöpolitiikka; cleaner production; Hazardous Waste; material efficiency; negotiated environmental agreements; policy instruments; waste prevention; pollution prevention; hazardous waste